Obesità e lavoro: proposta di un modello di intervento multidisciplinare per la prevenzione e sua applicazione in una industria metalmeccanica del Nord Italia / Obesity and work: proposal for a multidisciplinary intervention model for prevention and its application in an engineering plant - Vigna, L.; Agnelli, G.M.; Tirelli et al., A.S. (La Medicina del Lavoro, 2011)
«Obesity and work: proposal for a multidisciplinary intervention model for prevention and its application in an engineering plant». Introduction: Obesity is often particularly burdensome for subjects at work and leads to hypertension and diabetes preceded by a low grade of inflammation. Measures to promote health at the workplace can be achieved through periodic health surveillance. Simple parameters such as height, weight, body mass index (BMI), waist circumference (CV), blood pressure (BP), as well as taking into account the type of work and tasks, shift work and smoking, are in fact sufficient to identify the most significant features of the working population so as to adequately design the type of intervention required. The paper describes how a health promotion programme aimed at preventing overweight and obesity was implemented based on analysis of the health surveillance data routinely collected by the occupational physician in an engineering plant in northern Italy. Subjects and methods: Data on weight, height and BMI were collected for 301 workers with different jobs and shifts in an engineering plant; 32 of these workers, (mean age 44±8.4) agreed to undergo a diagnosis and treatment programme at the Obesity and Work Centre of the Clinica del Lavoro in Milan. Interventions and results: A higher incidence of overweight and obesity was found compared to the national average for similar age classes, therefore meetings were organized at the plant on awareness and information on correct lifestyle and diet targeted for shift workers. The workers who had followed the diagnosis and treatment programme had a mean BMI of 32.6 (SD 2.7) and, considering the parameters investigated, the presence of metabolic syndrome was found in a greater proportion of subjects (62.5%) than the average in our practice (46%) and particularly in workers with three day shifts. Conclusions: The intervention programme began with assessment of the information obtained in the course of routine periodic health surveillance according to the occupational hazards under study. On the basis of this information it was possible to implement the first awareness campaigns. On completion of the multidisciplinary intervention, which was conducted in collaboration with the occupational physician, two major initiatives were taken: one in the canteen with the aim of improving the nutritional content and type of meals offered to suit the dietary needs of overweight or obese workers, and the other consisted of an agreement with local gyms so as to motivate workers to exercise more. A prerequisite for this type of initiative is the willingness and understanding of the management to recognize the health of the worker as a priority value.